Terminological, Evaluative, and Interventional Plurality in Adolescent Internet Addiction: A Systematic Review - Raposo-Rivas, Manuela (2023)
Objective. The study aims to analyze the scientific production on Internet addiction in adolescents. Methodology. A systematic review, following PRISMA guidelines, was conducted on articles published between 2010 and 2020 in journals indexed in PubMed, Web of Science, Scopus, and ERIC databases. To conduct the review, a parameterized search was performed using the following keywords: Internet, adolescents, addiction, treatment, prevention, education, problematic use, abusive use and excessive use. They were combined with the Boolean operator AND. After an initial identification of 319 items, 24 met inclusion criteria related to thematic appropriateness, language, and age of beneficiaries. The instruments and interventions were reviewed and analysed inductively in terms of designations, prevalence, and incidence. Results. This review revealed a lack of consensus in the terminology used and in the measuring instruments, a poor educational approach, and low effectiveness of the interventions used. Conclusions. The interest of the results obtained lies in making possible a series of recommendations that will contribute to a better approach to this problem: standardizing the terminology and conceptualization used to refer to this field of study and unifying the measuring instruments, as the current ones yield very different data. Finally, in order to help alleviate Internet addiction among adolescents, the study  identified the need to develop prevention and educational intervention programs, promoted by public administrations, which allow access to all groups, especially the most vulnerable.